PRODUCTION SCHEDULING APPROACH BY ARENA SIMULATION AT PT. TRITUNGGAL PUTRA PERKASA - Susiati, Devi; Apriliana S.W, Indah (Inscientech: Journal of Industrial, Science and Technology, 2017)
This research was conducted at PT. Tritunggal Putra Perkasa, which manufactures a wide range of shoes. Subject matter in this research is applying the method of approach to the simulation of production scheduling in the Arena. This is done because the company often experience delays in order so that the fulfillment of consumer needs cannot be met. Process in the manufacture of shoes includes a process of cutting, printing, sewing, assembling and packaging. Before using ARENA simulation, this research compares the first production scheduling between conventional by using a method of the CPM (Critical Path Method), then use the simulation Arena. Scheduling production of the company in March with the arrival of as much as five orders. This company spent 36 days with 3 days delay experience with sequencing work of A-B-C-D-E, delays occurred in the work of c. results from the application of the CPM method i.e. spent 36 days but not delay occurs with sorting jobs A-B-C-DE. After that is done the application of simulated scheduling in the production Arena, so take only 34 days with sorting jobs A-B-C-D-E. So the company will not experience the delay and gain the trust of the buyer.  Keywords: Conventional, CPM, Simulation, Arena